Distinct communities of Cercozoa at different soil depths in a temperate agricultural field. Issue 4 (27th March 2019) - Degrune, Florine; Dumack, Kenneth; Fiore-Donno, Anna Maria; Bonkowski, Michael; Sosa-Hernández, Moisés A; Schloter, Michael; Kautz, Timo; Fischer, Doreen; Rillig, Matthias C
ABSTRACT: Protists are the most important predators of soil microbes like bacteria and fungi and are highly diverse in terrestrial ecosystems. However, the structure of protistan communities throughout the soil profile is still poorly explored. Here, we used Illumina sequencing to track differences in the relative abundance and diversity of Cercozoa, a major group of protists, at two depths; 10–30 cm (topsoil) and 60–75 cm (subsoil) in an agricultural field in Germany. At the two depths, we also distinguished among three soil compartments: rhizosphere, drilosphere (earthworm burrows) and bulk soil. With increasing depth, we found an overall decline in richness, but we were able to detect subsoil specific phylotypes and contrasting relative abundance patterns between topsoil and subsoil for different clades. We also found that the compartment effect disappeared in the subsoil when compared to the topsoil. More studies are now needed to describe and isolate these possibly subsoil specific phylotypes and better understand their ecology and function. Abstract : The soil profile from a temperate agricultural field in Germany displays distinct communities of Cercozoa, with the subsoil (∼60 cm) hosting specific phylotypes.